Sodium-Glucose Co-transporter-2 Inhibitor of Dapagliflozin Attenuates Myocardial Ischemia/Reperfusion Injury by Limiting NLRP3 Inflammasome Activation and Modulating Autophagy - Yu, Yong-Wei; Que, Jia-Qun; Liu, Shuai; Huang, Kai-Yu; Qian, Lu; Weng, Ying-Bei; Rong, Fang-Ning; Wang, Lei; Zhou, Ying-Ying; Xue, Yang-Jing; Ji, Kang-Ting (Frontiers in Cardiovascular Medicine, 2022)
Background: The sodium-glucose co-transporter-2 (SGLT-2) inhibitor dapagliflozin improves cardiovascular outcomes in patients with type 2 diabetes in a manner that is partially independent of its hypoglycemic effect. These observations suggest that it may exert a cardioprotective effect by another mechanism. This study explored the effects of dapagliflozin on myocardial ischemia/reperfusion injury in a mouse model. Materials and Methods: For the in vivo I/R studies, mice received 40 mg/kg/d dapagliflozin, starting 7 days before I/R. Evans Blue/TTC double-staining was used to determine the infarct size. Serum levels of cTnI, CK-MB, and LDH were measured. Inflammation, autophagy protein expression, and caspase-1 activity changes were measured at the protein level. Primary cardiomyocytes were used to investigate the direct effect of dapagliflozin on cardiomyocytes and to verify whether they have the same effect as observed in in vivo experiments. Result: A high dose of dapagliflozin significantly reduced infarct size and decreased the serum levels of cTnI, CK-MB, and LDH. Dapagliflozin also reduced serum levels of IL-1β, reduced expression of myocardial inflammation-related proteins, and inhibited cardiac caspase-1 activity. The treatment restored autophagy flux and promoted the degradation of autophagosomes. Relief of inflammation relied on autophagosome phagocytosis of NLRP3 and autophagosome clearance after lysosome improvement. 10 μM dapagliflozin reduced intracellular Ca2+ and Na+ in primary cardiomyocytes, and increasing NHE1 and NCX expression mitigated dapagliflozin effects on autophagy. Conclusion: Dapagliflozin protects against myocardial ischemia/reperfusion injury independently of its hypoglycemic effect. High-dose dapagliflozin pretreatment might limit NLRP3 inflammasome activation and mediate its selective autophagy. Dapagliflozin directly acts on cardiomyocytes through NHE1/NCX.